Dari Teks ke Hidup: Peran Katekese Literer dalam Memahami Sabda Allah bagi Kaum Muda - Marini Marini; Intansakti Pius X (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the role of literary catechesis in helping believers, especially young people, to understand and live out the Word of God in their daily lives. The background of this research is rooted in the rapid development of technology and the flow of information, which significantly influence how young people perceive and experience their faith. In this context, catechesis is often still conducted in a one-way manner and tends to lack connection with participants’ lived experiences. Therefore, a more contextual and participatory approach is needed. This research employs a literature study method by analyzing various sources, including academic journals and Church documents, particularly the Petunjuk untuk Katekese (2020). The findings show that literary catechesis is an effective approach because it places Sacred Scripture at the center of faith formation through processes of reading, understanding, and reflecting on the text. This approach enables participants not only to know the content of Scripture but also to relate it to their personal life experiences.